Raw materials for Irish animal husbandry - Johnston, Joseph (Statistical and Social Inquiry Society of Ireland, 1951)
There are three possible objectives for agricultural production. One may produce cash crops for direct human consumption. This, of course, involves tillage. One may produce animal products also for human consumption; In those few countries in which grass will grow readily this in some form?as grass, as hay or as silage? is the cheapest of all raw materials for animal product production. But tillage is also necessary in order to supplement the deficiencies of grass?fresh or preserved?as winter feed for cattle, and also in order to provide food for those animals, e.g. pigs, which can only make use of grass to a limited extent. The tillage need not necessarily take place on a farm which specialises in animal products, but the products of tillage must be available from some source, native or external, if such a farm is to specialise in animal product production. The third possible objective of agricultural activity is the production of raw materials for industry. The growing of cotton, jute, or flax are typical examples of the third objective. Agriculture in Eire is only concerned to a limited extent with this form of production but in Northern Ireland the growing of flax is quite important. There are a few areas in Eire also in which flax is grown.
Read before the Society, 8 December 1950
Keywords: Raw materials for livestock industry; Animal husbandry; Farm inputs; Irish agriculture; 314.15